Pricing Strategies and Consumers Purchasing Decisions in Small and Medium Enterprises in Benin City, Edo State - Agbonifoh, Christopher Ihionkhan; Okodugha, Nathaniel (NIU Journal of Social Sciences, 2025)
This study examined the pricing strategies employed by Small and Medium Enterprises (SMEs) in Benin City and their impact on purchasing decisions. A quantitative research design was adopted, and a structured questionnaire was administered to 311 respondents. The results show that SMEs in Benin City prioritize offering competitive prices, discounts, and bundled packages to attract customers. Price transparency was found to be critical in building trust with customers and influencing purchasing decisions. The correlation analysis revealed significant relationships between price transparency, price discount, and price bundling, and purchasing decisions. The regression model identified price transparency as the most significant predictor of purchasing decisions. The study concludes that SMEs in Benin City should prioritize transparency in their pricing strategies to attract and retain customers. The findings provide valuable insights for SMEs in Benin City, highlighting the importance of competitive pricing, discounts, bundled packages, and price transparency in driving business success. Recommendations are made for SMEs to improve price transparency, offer competitive prices, use price bundling strategically, invest in customer education, and monitor and adjust pricing strategies regularly. Keywords: Competitive Pricing, Pricing Strategies, Purchasing Decisions, Price Transparency, Small and Medium-sized Enterprises (SMEs)